Research Ethics: advances and challenges - DOI: 10.3395/reciis.v2.Sup1.212en - Dirce Guilhem (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
The topic of research ethics is part of the scientific agenda in distinct areas of knowledge. The diversity of the aspects involved shows the complexity of the dilemmas that emerge in this scenario. This paper pays special attention to four points that deserve reflexion, be they in the international or in a Brazilian context: the existing link between method and research ethics, the process of training and strengthening young scientists, the defense of a single standard for international collaborative studies, and the proposal to revise the current text of the Helsinki Declaration. The analysis of these points permits to verify that significant advances in this field have occurred; however, the constant attempts to loosen the ethical requirements used to guide scientific practice could cause a backslide that would bring serious consequences for research participants. Brazil is a privileged country because the Brazilian system for ethical review of researches (the System CEP/Conep - Research Ethics Committees and Brazilian National Commission on Research Ethics) is linked to democratic control, which guarantees the originality and legitimacy the system needs in order to defend the interests and rights of subjects who participate in research.